Lumbar Dorsal Root Ganglion Stimulation Lead Placement Using an Outside-In Technique in 4 Patients With Failed Back Surgery Syndrome: A Case Series. Issue 10 (August 2020) - Chapman, Kenneth B.; Nagrani, Sohan; Patel, Kiran V.; Yousef, Tariq; van Helmond, Noud
Abstract : Dorsal root ganglion stimulation (DRG-S) has shown promise as a treatment for low back pain. The traditional anterograde placement of DRG-S leads can be challenging in patients with anatomical changes from prior back surgery. We describe an "outside-in" placement technique of DRG-S leads in 4 patients with histories of multiple lumbar surgeries, which made the traditional anterograde placement not feasible. At long-term follow-up, the patients experienced substantial pain relief and improvement in quality of life, with no complications. The outside-in lead placement technique may be an efficacious alternative to the traditional techniques in patients with anomalous anatomy from prior surgery.